An Evaluation of Application of Zakat for Poverty Alleviation among Muslims in Iba Housing Estate, Lagos State, Nigeria - Kabir Olawale Paramole (International Journal of Zakat, 2020)
No Islāmic Scholar in Lagos State will deny the fact that, Zakāt is the most abandoned out of the five pillars of Islām . Even, the few affluent Muslims who pay attention to it may not be perfect in its annual deduction and disbursement. This study assessed and evaluated the application of Zakāt as employed by Iba Housing Estate Zakāt Agency for Poverty Alleviation with a view of determining its success in ameliorating poverty among Muslims in the community. Using field and library based researches; it has been found that the agency has recorded a very little success in its few years of operation with the small fund available to operate upon. Its best practices include, rendering of support and assistance to the needy and the poor challenged with health problems, widows, orphans etc. within the area. However, the sources of income of the agency are circumscribed to only Zakāt payment which cannot create an avenue for outstanding impacts. The study recommends among others, that in order to contribute immensely to reduce poverty, as well as to be able to cover the needs of the poor Muslims in the community, the agency should diversify its efforts in getting more funds from other lawful sources, groups, agencies and wealthy individuals who have been showing interest in supporting their cause.